2020
DOI: 10.21037/atm-20-3875
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of 1,641 cases of classic fever of unknown origin

Abstract: Background: Fever of unknown origin (FUO) is commonly defined as fever higher than 38.3 ℃ on several occasions during at least 3 weeks with uncertain diagnosis after a number of obligatory investigations. It is a special type of fever and a common disease in internal medicine. However, due to its complex etiology, lack of characteristic clinical manifestations, and insufficient laboratory examination indicators, it often baffles clinicians in diagnosis. We herein present a study of the etiological factors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
3
19
1
Order By: Relevance
“…In a large retrospective study, which set out to analyse 1641 patients with fever of unknown origin (FUO), AoSD was responsible for 5.4% of cases [ 36 ]. Overall, rheumatic diseases comprise approximately 30% of cases with FUO, with AoSD being the most frequent group [ 37 ].…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…In a large retrospective study, which set out to analyse 1641 patients with fever of unknown origin (FUO), AoSD was responsible for 5.4% of cases [ 36 ]. Overall, rheumatic diseases comprise approximately 30% of cases with FUO, with AoSD being the most frequent group [ 37 ].…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…Previous studies merely focused on the total population of lymphoma patients with FUO. 3,15,16 In Zhou et al's study, 15 the median age of lymphoma patients with FUO was 42 years old and the prevalence of male was 48.3%. In our study, the median age of the FUO group in NK/T-CL was 42.0 years old, which was consistent with Zhou's study.…”
Section: Discussionmentioning
confidence: 96%
“…The laboratory examinations of lymphoma patients with FUO were usually abnormal according to previous studies. 15,16 In our study, further subgroup analyses were performed to compare the differences in laboratory index between the FUO and non-FUO groups strati ed with four pathological subtypes. Our study found that, for patients with B-NHL or T-NHL, there was a higher incidence of EBV positive in the FUO group.…”
Section: Discussionmentioning
confidence: 99%
“…Fever of unknown origin can be attributed to many factors, including infection (40%), neoplastic disease (20%), collagen-vascular disease (15%) and so on ( 16 ). A retrospective study found that tuberculosis was the most common cause of infectious fever and lymphoma was the most common cause of neoplastic fever ( 17 ). In this case, the hemogram and blood biochemistry of the patient were basically normal, CRP and ESR were slightly elevated, indicating inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%